2009
DOI: 10.1021/ja904711k
|View full text |Cite
|
Sign up to set email alerts
|

Similar Energetic Contributions of Packing in the Core of Membrane and Water-Soluble Proteins

Abstract: A major driving force for water soluble protein folding is the hydrophobic effect, but membrane proteins can not make use of this stabilizing contribution in the apolar core of the bilayer. It has been proposed that membrane proteins compensate by packing more efficiently. We therefore investigated packing contributions experimentally by observing the energetic and structural consequences of cavity creating mutations in the core of a membrane protein. We observed little difference in the packing energetics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 20 publications
3
70
0
Order By: Relevance
“…Changes in stability seem to be related to changes in intramolecular interactions, presumably through packing effects and/or disruption of specific weak interactions such as the hydrogen bond between E204A and S194. These observations are in keeping with recent suggestions that packing energetics (9,43) and side-chain burial (44) play a key role in membrane protein stability. The destabilizing mutations we identified in helix G were subject to a Φ-value analysis to characterize the folding transition state.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in stability seem to be related to changes in intramolecular interactions, presumably through packing effects and/or disruption of specific weak interactions such as the hydrogen bond between E204A and S194. These observations are in keeping with recent suggestions that packing energetics (9,43) and side-chain burial (44) play a key role in membrane protein stability. The destabilizing mutations we identified in helix G were subject to a Φ-value analysis to characterize the folding transition state.…”
Section: Discussionsupporting
confidence: 91%
“…increase in Ca ++ -permeability might be facilitated by the formation of a more flexible structure and thus the formation of a cavity, as shown for the L94A mutation of the lightdriven proton pump bacteriorhodopsin (compare Fig. 1) 21 . This cavity would be located in a hydrophobic patch as part of the conserved transmembrane helix three (TM3), only a helical turn apart from C128.…”
Section: Application To Hippocampal Neuronsmentioning
confidence: 75%
“…17 We have found that membrane proteins increase van der Waals packing contributions relative to soluble proteins by increasing the overall level of side-chain burial, rather than by improved packing efficiency (volume occupied by atoms). 18,19 Nevertheless, either increased packing efficiency or increased burial could be an important factor in stabilizing membrane proteins in hot environments. 15 We therefore investigated whether packing density and burial are different in mesophiles and thermophiles.…”
Section: Burial and Packingmentioning
confidence: 99%